Pentingnya Manajemen Bisnis Dalam Mengembangkan Usaha - Aji Pramudya; Era Yunita; Laila Ali Tanjung; Suwandi S (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Developing a business is a very important thing to do in running a business. This is because a business that continues to grow is a sign of a business that is running well and is stable. Apart from that, along with increasingly tight business competition, it is necessary to make efforts to develop business continuously so that the business managed can survive. Business management in building a business is mandatory, because the success or failure of a business depends on management management which includes resources, products. , production and marketing. Developing a business strategy is the initial foundation of a healthy business. This is useful for planning, designing how your business will run in the future, as well as reducing the level of risk of loss and problems that often occur in the field.